Protective effects of psoralen polymer lipid nanoparticles on doxorubicin - induced myocardial toxicity - Fansu Meng; Yong Ouyang; Qianqian Ma; Manling Du; Hui Liu; Yong Zhuang; Mujuan Pang; Tiange Cai; Yu Cai (Universidade de São Paulo, 2022)
Abstract Doxorubicin (DOX) induced myocardial toxicity may limit its therapeutic use in clinic. Psoralen (PSO), a major active tricyclic furocoumarin extracted from Psoralea corylifolia, is widely used as an antineoplastic agent in treatment of leukemia and other cancers. This study is aim to find the protective effect of psoralen polymer lipid nanoparticles (PSO-PLN) on doxorubicin-induced myocardial toxicity in mice. The model of myocardial toxicity induced by DOX was established. The experiment was divided into 6 groups: normal saline group, DOX + Sulfotanshinone Sodium, DOX + PSO-PLN (3 mg/kg), DOX + PSO-PLN (6 mg/kg), DOX + PSO-PLN (9 mg/ kg), DOX group. DOX alone treated mice lead to a significant decrease in the body weight, heart weight, and increase in the serum levels of lactate dehydrogenase (LDH), creatine kinase (CK) and malondialdehyde (MDA) markers of cardiotoxicity. However, DOX reduced glutathione (GSH) content and activities of antioxidant enzymes, including superoxide dismutase (SOD) and glutathione peroxidase (GPX), were recovered by PSO-PLN. And PSO-PLN also decreased markers of cardiotoxicity in the serum. Western blotting data showed that the protective effects of PSO-PLN might be mediated via regulation of protein kinase A (PKA) and p38. Our study suggest that PSO-PLN possesses antioxidant activities, inactivating PKA and p38 effect, which in turn protect the heart from the DOX-induced cardiotoxicity.